Method to generate the pseudo random sequence based on the statistical properties - Sen BAI; Long-fu ZHOU; Hui GUO; Bing YAN (网络与信息安全学报, 2017)
There are some problems existing in pseudo-random sequence generating methods, such as the weaker proportionality, bad run length characteristic, etc. Hence, based on the SimiHam algorithm in Knight's tour problem, a pseudo-random sequences generating method was proposed according to the statistical properties of random se-quence. First, set runs value 0 and 1 in different length for the grids in chessboard, and then scan the chessboard with Hamilton cycles which are generated by SemiHam algorithm in Knight's tour problem, At last extract run length values of 0 and 1 and get the pseudo-random sequences. Experimental results show that the pseudo-random se-quence generated by the proposed algorithm satisfies the statistical properties of a random sequence and has better randomness.